Моделювання вигину двошарової структури при термовпливах - Невлюдов, І. Ш.; Палагін, В. А.; Демська, Н. П.; Разумов-Фризюк, Є. А. (ХНУРЕ, 2019)
The article proposes a mathematical model for the calculation of the bending of two-layer aluminum-polyamide film materials, which is based on the general provisions of the theory of bending: the presence of a neutral layer, the length of which does not change during bending, the material is on the side of concavity, prone to compression, and Finally, the structure obeys the Hooke law, which makes it possible to calculate stresses in layers of material by removing them from the neutral layer.
Keywords: mathematical model; two-layer aluminum-polyamide film materials; thermal effect